Challenges for Developing Palliative Care Services in Resource- Limited Settings of Kazakhstan - Islam Salikhanov; Stephen R. Connor; Gulnara Kunirova; Fatima Khashagulgova; Gulzhaina Nazarova; Byron Lawrence Crape; Maria C. Katapodi (Frontiers Media S.A., 2023)
Background: Approximately 40 million people in need of palliative care worldwide, while 80% of them live in low- and middle-income countries. Kazakhstan, a low-to middle-income country with a reforming healthcare system, is committed to improving quality and accessibility of care for its 100,000 terminal patients in need of palliative care.Policy Options and Recommendations: To join the group of countries where palliative care is available, accessible, and affordable, Kazakhstan must integrate palliative services into the mainstream healthcare system at all levels, from primary healthcare to hospices, and from major cities to remote villages. Based on the evidence thoroughly collected directly from the Ministry of Health, authors propose a feasible set of recommendations regarding palliative policy, pain relief, infrastructure, workforce, and education, which could be implemented in LMICs beyond Kazakhstan.Conclusion: This study presents an analysis of challenges, recent developments, and needs of palliative care in Kazakhstan, including funding, policy, workforce, education, and infrastructure, providing an evidence base and recommendations for future development of palliative care in Kazakhstan and in other LMICs.